Prevalence and Predisposing Factors of Post Renal Transplant Erythrocytosis - Mazharulhaq, Aimal Khan, Taleah Tahir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Aim of current study was to determine the factors and prevalence of post-transplant erythrocytosis after kidney transplantation. Study Design: Retrospective study Place and Duration: Institute of Kidney Diseases Hayatabad Peshawar during June 2021 to December 2021. Methods: Total 118 patients of renal transplant were presented. Participants' full demographic information was recorded after getting written consent from each participant. Association of risk factors and prevalence of post-transplant erythrocytosis were recorded. Hematocrit (Ht) above 52% and haemoglobin (Hb) over 18 g/dl in males and Ht over 50% and Hb over 17 g /dl in females were considered to be indicative of true PTE. We used SPSS 18.0 to analyze all data. Results: The mean age of the patients was 50.6±2.31 years with mean BMI 27.4±11.52 kg/m2. There were majority 76 (64.4%) patients were males and 42 (35.6%) patients were females. Frequency of PTE was found in 23 (19.5%) cases and 95 (80.5%) cases were without PTE. Most common factors for PTE development were endogenous erythropoietin, local renal hypoxia, endogenous androgens, insulin-like growth factors and the renin-angiotensin- aldosterone system. Mean duration of dialysis in PTE group was 25.1±7.48 months and duration of patients without PTE was 51.9±6.75 months. Frequency of diabetes, hypertension, glomerulonephritis, polycystic kidney disease and graft failure were higher in PTE patients as compared to non-PTE. We found higher number of acute rejection in PTE patients as compared to non PTE cases with p value <0.009. Conclusion: We concluded in this study that the shorter duration of dialysis and higher number of acute rejection before kidney transplant were the risk factors for post transplant erythrocytosis. Most common factor for PTE development was renin-angiotensin- aldosterone system. Keywords: Erythrocytosis, Transplantation, Kidney, Dialysis